CSF‐1‐activated macrophages are target‐directed and essential mediators of schwann cell dedifferentiation and dysfunction in Cx32‐deficient mice. Issue 6 (27th January 2015) - Groh, Janos; Klein, Ines; Hollmann, Claudia; Wettmarshausen, Jennifer; Klein, Dennis; Martini, Rudolf
Abstract : We investigated connexin 32 (Cx32)‐deficient mice, a model for the X‐linked form of Charcot‐Marie‐Tooth neuropathy (CMT1X), regarding the impact of low‐grade inflammation on Schwann cell phenotype. Whereas we previously identified macrophages as amplifiers of the neuropathy, we now explicitly focus on the impact of the phagocytes on Schwann cell dedifferentiation, a so far not‐yet addressed disease‐related mechanism for CMT1X. Using mice heterozygously deficient for Cx32 and displaying both Cx32‐positive and ‐negative Schwann cells in one and the same nerve, we could demonstrate that macrophage clusters rather than single macrophages precisely associate with mutant but not with Cx32‐positive Schwann cells. Similarly, in an advanced stage of Schwann cell perturbation, macrophage clusters were strongly associated with NCAM‐ and L1‐positive, dedifferentiated Schwann cells. To clarify the role of macrophages regarding Schwann cell dedifferentiation, we generated Cx32‐deficient mice additionally deficient for the macrophage‐directed cytokine colony‐stimulating factor (CSF)−1. In the absence of CSF‐1, Cx32‐deficient Schwann cells not only showed the expected amelioration in myelin preservation but also failed to upregulate the Schwann cell dedifferentiation markers NCAM and L1. Another novel and unexpected finding in the double mutants was the retained activation of ERK signaling, a pathway which is detrimental for Schwann cell homeostasis in myelin mutant models. Our findings demonstrate that increased ERK signaling can be compatible with the maintenance of Schwann cell differentiation and homeostasis in vivo and identifies CSF‐1‐activated macrophages as crucial mediators of detrimental Schwann cell dedifferentiation in Cx32‐deficient mice. GLIA 2015;63:977–986 Main Points: In heterozygous Cx32def mice macrophage clusters precisely associate with mutant but not with wt Schwann cells. When macrophage activity is blocked, mutant Schwann cells do not dedifferentiate and are preserved from damage despite retained ERK activation.